Lithofacies Associations and Paleocurrent Patterns in the Nagri Formation of the Siwalik Group in Kach-Zarghun Area of Northeast Baluchistan - Kassi, Akhtar Mohammad; Qureshi, Amjad Rashid; Kakar, Din Muhammad (Journal of Himalayan Earth Sciences, 1990)
The Nagri Formation of the Siwalik Group contains at least eight distinct lithofacies types, the most dominant, in descending order, being the horizontal bedded sandstones (Sh) mixed with the low angle crossbedded types (Sl) and the trough crossbedded sandstone (St) which are mostly very coarse grained, pebbly and poorly sorted. Other lithofacies like the massive sandstones (Sm) and also those having erosional scours along with mud interclasts at their base (Se), plannar crossbedded sandstones (Sp), massive sandstones with slump structures(Ssm), laminated slump sandstones (Ssl) and the occasional finely laminated siltstones and mudstones (Fl) are also observable. These associations suggest frequent surges of high energy floods with antidunes, scourfills and plannar bed flows along with periods of normal flows causing dunes and ripples. Paleocurrrent patterns based on directions of maximum inclination of foreset beds in trough crossbedded sandstones of the Nagri Formation suggest a northerly and southeasterly derivation in the Spera Ragha-Gogai Syncline north of Kach Thanna and a dominant north and northeasterly derivation in Pasta-Zarghun Synclines south of Kach Thanna. These patterns suggest that basin was deriving its detritus from a landmass to the north of Zarghun, east of Gogai and south of Spera Ragha. Horuever, paleocurrents on the northern flank of Spera Ragha-Gogai Synclines suggest derivation also from a landmass to the north of Rud Malazai, Malkhezun and Umai.